A new method to measure the beta function in a Paul trap - Martin, L; Ito, K; Kelliher, D; Machida, S; Okamoto, H; Sheehy, S (Joint Accelerator Conferences Website, 2018)
The Simulator of Particle Orbit Dynamics (S-POD) is a linear Paul trap at Hiroshima University, Japan, used to study beam physics. S-POD has so far been used to study resonances in high intensity beams, predominantly using a simple alternating gradient lattice configuration. Recently a similar apparatus, the Intense Beam Experiment (IBEX), has been constructed at the Rutherford Appleton Lab in the UK. To use either of these experiments to study beam dynamics in more complex lattice configurations in the future, further diagnostic techniques must be developed for Paul traps. Here we describe a new method to measure the beta function and emittance in a Paul trap.